2015
DOI: 10.1515/hmbci-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Pro-nerve growth factor in the ovary and human granulosa cells

Abstract: Background Pro-nerve growth factor must be cleaved to generate mature NGF, which was suggested to be a factor involved in ovarian physiology and pathology. Extracellular proNGF can induce cell death in many tissues. Whether extracellular proNGF exists in the ovary and may play a role in the death of follicular cells or atresia was unknown. Material and Methods Immunohistochemistry of human and Rhesus monkey ovarian sections was performed. IVF-derived follicular fluid and human granulosa cells were studied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In contrast, ICIs as single agents have not shown meaningful benefit for proficient MMR tumors (8), which are the vast majority of GI cancer cases. MSI-H tumors account for 6-22% of gastric, 1% of pancreatic, 3% of liver, and 14-16% of colorectal cancers (22)(23)(24)(25)(26)(27). Antibodies against PD-1/programmed death-ligand 1 (PD-L1) or cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) are the most clinically advanced immunotherapy in cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, ICIs as single agents have not shown meaningful benefit for proficient MMR tumors (8), which are the vast majority of GI cancer cases. MSI-H tumors account for 6-22% of gastric, 1% of pancreatic, 3% of liver, and 14-16% of colorectal cancers (22)(23)(24)(25)(26)(27). Antibodies against PD-1/programmed death-ligand 1 (PD-L1) or cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) are the most clinically advanced immunotherapy in cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…We will then present recent data, which implicate necroptotic cell death in GCs and in human CL regression. We will here not discuss studies, which identified further factors of potential relevance to ovarian follicular fate, e.g., handling of catecholamines and generation of H 2 O 2 (59).…”
Section: Introduction and Scopementioning
confidence: 99%
“…The increase in the biosynthetic enzymes for ACh indicate that NGF regulates ovarian ACh production. Previous reports also suggest that NGF stimulates ACh production (6,9,10). This increase could protect follicular development from the actions of an over-activated sympathetic pathway and chronic increase in ovarian noradrenaline, caused by the hyperinnervation of the organ (39,40).…”
Section: Discussionmentioning
confidence: 80%
“…The nerve growth factor (NGF) was the first neurotrophic factor found to regulate ovarian noradrenergic neurons ( 8 ). NGF is one of the most important factors in the regulation of cholinergic neurons in the central nervous system ( 9 , 10 ), but there is limited information on its action in the ovary. If this is correct, we either can suggest that NGF acting on sympathetic nerves increases NE in the ovary by a direct effect of NGF or induced by stress ( 11 , 12 ) and can participates in the development of the PCO phenotype in rat.…”
Section: Introductionmentioning
confidence: 99%